Is the Eurozone not a monetary union, but an extraordinary exchange rate union? - Beate Sauer; Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2013)
The Target imbalances within the Eurozone can be interpreted as a sign of a missing balance of payments adjustment mechanism for the member countries. As the Eurozone lacks a fiscal union, in economic theory it is more an exchange rate union or a system of fixed exchange rates than a monetary union. In the latter, there would not be any national balances of payments, but only one for the whole Eurozone. This paper will show why the Target System is a crucial indicator for the Eurozone not being a monetary union, but an exchange rate union and why countries holding Target liabilities against the European System of Central Banks can be compared to a reserve currency country, e.g. like the US during the Bretton-Woods-System.
Keywords: E40; E41; E42; E50; E52; 330; Target Imbalances; Balance of Payments Crisis; Balance of Payments Adjustment Mechanism; Eurozone; Fixed Exchange Rates; Fiscal Union